2015
DOI: 10.1534/genetics.115.184432
|View full text |Cite
|
Sign up to set email alerts
|

Combined Interactions of Plant Homeodomain and Chromodomain Regulate NuA4 Activity at DNA Double-Strand Breaks

Abstract: DNA double-strand breaks (DSBs) represent one of the most threatening lesions to the integrity of genomes. In yeast Saccharomyces cerevisiae, NuA4, a histone acetylation complex, is recruited to DSBs, wherein it acetylates histones H2A and H4, presumably relaxing the chromatin and allowing access to repair proteins. Two subunits of NuA4, Yng2 and Eaf3, can interact in vitro with methylated H3K4 and H3K36 via their plant homeodomain (PHD) and chromodomain. However, the roles of the two domains and how they inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 62 publications
(102 reference statements)
1
6
0
Order By: Relevance
“…As described above and in previous studies [9,10,14,33], Eaf3 CD itself has high methylation specificity but low sequence specificity; therefore, combinatorial actions with the PHD of Yng2 in NuA4 and with the PHD of Rco1 in Rpd3S are necessary for the overall affinity and specificity of the H3K4me-and H3K36me-nucleosome interaction [12,16], and activation [15,38,39] of the complexes (Figure 7). A biochemical study previously demonstrated that Rpd3S preferentially binds di-nucleosomes by contacting two nucleosomes simultaneously via Eaf3 CD and Rco1 PHD [40].…”
Section: Discussion Eaf3 CD Offers Ph Sensitivity To the Regulation Osupporting
confidence: 64%
See 1 more Smart Citation
“…As described above and in previous studies [9,10,14,33], Eaf3 CD itself has high methylation specificity but low sequence specificity; therefore, combinatorial actions with the PHD of Yng2 in NuA4 and with the PHD of Rco1 in Rpd3S are necessary for the overall affinity and specificity of the H3K4me-and H3K36me-nucleosome interaction [12,16], and activation [15,38,39] of the complexes (Figure 7). A biochemical study previously demonstrated that Rpd3S preferentially binds di-nucleosomes by contacting two nucleosomes simultaneously via Eaf3 CD and Rco1 PHD [40].…”
Section: Discussion Eaf3 CD Offers Ph Sensitivity To the Regulation Osupporting
confidence: 64%
“…In fact, Eaf3 CD can also bind weakly to H3K4me, facilitating recruitment of NuA4 to the promoter region. Similar to Rpd3S, the PHD of the Yng2 subunit of NuA4 plays an essential cooperative role in binding of Eaf3 CD to H3K4me [15,16]. Thus, Eaf3 CD seems to have no strong sequence specificity and can bind to both H3K4me and H3K36me, while the specific recruitment of NuA4 and Rpd3S to H3K4me and H3K36me, respectively, is cooperatively determined by the PHD of the respective Yng2 and Rco1 subunits.…”
Section: Introductionmentioning
confidence: 99%
“…During the last steps of preparation of the manuscript, a report implicating the combined action of Eaf3 CHD/H3K36me and Yng2 PHD/H3K4me in assisting NuA4 function during the repair of DNA double-strand breaks was published (67). While the concept is interesting, in our hands we could not detect any increased sensitivity to DNA-damaging agents for either our single or double mutant cells (20,54) (Fig.…”
Section: Discussionmentioning
confidence: 65%
“…Indeed, several studies have shown that the methylated H3K4 and H3K36 interact with PHD and chromodomain within the NuA4 complex by using the GST pull-down, immunoprecipitation and protein array assays ( 9 , 11 , 12 ). Furthermore, the set1Δ set2Δ mutants or mutants with combined mutations of the PHD and chromodomains show defective acetyltransferases activity of NuA4 ( 33 , 34 ). Additionally, an experiment has shown that the interaction of H3K4me3 with Tudor domain in Sgf29 within the SAGA complex is also essential for the acetyltransferase activity of SAGA ( 35 ).…”
Section: Utility and Discussionmentioning
confidence: 99%